Brainstorming as an Effective Learning Strategy to Promote Students’ Critical Thinking Skills - Widiastuti, Ida Ayu Made Sri; Murtini, Ni Made Wersi; Anto, Ruli (FKIP Universitas Lampung, 2022)
Students’ critical thinking skill is vividly crucial to be developed to enable students to solve various problems in nowadays life. Objectives: This study investigates the brainstorming strategy employed by teachers in the classroom to enhance students’ critical thinking skills. Methods: This study employed a qualitative research approach conducted in a senior high school consisting of 30 teachers and 4 teachers were selected as the research participants. The data were collected by conducting semi-structured interviews and classroom observations. The data were analyzed descriptively to establish valid and reliable findings. Findings: This study found that teachers intensively used the brainstorming method in enhancing students’ critical thinking skills by asking various challenging questions to arouse students’ critical skills. Conclusions: the Findings of this study revealed the importance of conducting brainstorming strategies during the learning activities. Moreover, this study implies teachers should utilize the brainstorming method more intensively to develop students’ critical thinking skills. Keywords: brainstorming, strategy, teachers, promote, critical, skill.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202243